Adipose-derived stem cells from the breast - Yang, Jie; Xiong, Lingyun; Wang, Rongrong; Sun, Jiaming; Hirche, Christoph (Journal of research in medical sciences, 2014)
Background: - The adipose tissue is deemed as an ideal source of adipose-derived stem cells (ADSCs). Previous studies have reported that ADSCs can be isolated from several organs and locations; however, slight attention has been paid to the breast. We would like to report our experiences in isolating breast ADSCs (bADSCs). - - Materials and Methods: - Adipose tissues were harvested from the breasts of seven hypertrophic breast patients. Collagenase I was used to isolate the primary ADSCs. Surface markers were analyzed by flow cytometry. Cellular morphologies were observed. Proliferations of different passages were compared. Viabilities after the cryopreservation were evaluated. Adipogenic and osteogenic differentiation was induced. - - Results: - Primary cultured cells showed morphologies similar to fibroblasts, and expressed surface markers including CD13, CD44, CD90, and CD105. There was no statistical difference of proliferation between different passages (P > 0.05) and between with and without cryopreservation (P > 0.05). Additionally, isolated cells were differentiated into adipocytes and osteoblasts. - - Conclusion: - bADSCs may represent an alternative candidate for tissue engineering. Further studies are needed to obtain more comprehensive understanding on bADSCs.
Gesehen am 06.10.2020